2013
DOI: 10.3168/jds.2012-5964
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the growth of Listeria monocytogenes in mold-ripened cheeses

Abstract: This study presents possible applications of predictive microbiology to model the safety of mold-ripened cheeses with respect to bacteria of the species Listeria monocytogenes during (1) the ripening of Camembert cheese, (2) cold storage of Camembert cheese at temperatures ranging from 3 to 15°C, and (3) cold storage of blue cheese at temperatures ranging from 3 to 15°C. The primary models used in this study, such as the Baranyi model and modified Gompertz function, were fitted to growth curves. The Baranyi mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…The A f values within range 1.3–1.5 are also recognised as acceptable predictions. The calculated value of A f (1.08) for elaborated secondary model demonstrated that the predictions of the polynomial model are within acceptable limits (Ross, ; Giffel & Zwietering, ; Lobacz et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The A f values within range 1.3–1.5 are also recognised as acceptable predictions. The calculated value of A f (1.08) for elaborated secondary model demonstrated that the predictions of the polynomial model are within acceptable limits (Ross, ; Giffel & Zwietering, ; Lobacz et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…CP is based on experimental data generated in microbiological media. Higher values of GR generated with CP could have been caused by a lack of microbiota which competes for nutrients and is found in Camembert‐type cheese varieties as fermentation starters (Irlinger & Mounier, ; Lobacz et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important extrinsic factors limiting the growth and survival of microorganisms is the storage temperature of the product (Lobacz et al 2013). Mesophilic microorganisms, including S. aureus, show a lack of growth at temperatures of 4-6 o C. Growth temperatures of S. aureus were determined in the range of 7-48.5 o C (Valero et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These models are among the most commonly used mathematical models for modeling the survival of bacteria on the nonlinear nature of these changes (Xiong et al 1999, McKellar and Lu 2004, Huang 2009, Lobacz et al 2013.…”
Section: Discussionmentioning
confidence: 99%